Diseño de un plan de fluidos a nivel de laboratorio para las operaciones de perforación del yacimiento, completamiento y tratamiento enzimático en pozos nuevos del campo a en la cuenca Llanos Orientales (2018)
The following work is aimed at the design of a fluid plan at the laboratory level for the operations of reservoir drilling, completion and enzymatic treatment in new wells to be carried out in the Llanos Orientales basin. The focus of the project was on the formation damage that these fluids could generate when placed in contact with the reservoir area, seeking to mitigate the impact generated with the drilling fluid and the completion fluid and designing an enzyme-based fluid focused on reducing the damage generated by the drilling fluid. The first stage of the project consisted of a theoretical description of the fundamentals required to proceed to elaborate the proposed fluids, as well as an analysis of the fluid plan currently handled by the company through the recapitulation of the reports of the different programs carried out. Subsequently, the drilling fluid was designed for the reservoir area, using a trial and error dynamic, prioritizing the filtering tests and carrying out a validation of the properties through the use of the Bridgewise® and Advantage® programs.